2009
DOI: 10.1074/jbc.m807299200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phosphorylation and Basic Residues in the Catalytic Domain of Cytosolic Phospholipase A2α in Regulating Interfacial Kinetics and Binding and Cellular Function

Abstract: Group IVA cytosolic phospholipase A 2 (cPLA 2 ␣) is regulated by phosphorylation and calcium-induced translocation to membranes. Immortalized mouse lung fibroblasts lacking endogenous cPLA 2 ␣ (IMLF ؊/؊ ) were reconstituted with wild type and cPLA 2 ␣ mutants to investigate how calcium, phosphorylation, and the putative phosphatidylinositol 4,5-bisphosphate (PIP 2 ) binding site regulate translocation and arachidonic acid (AA) release. Agonists that elicit distinct modes of calcium mobilization were used. Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 70 publications
(108 reference statements)
2
68
0
Order By: Relevance
“…Increase in free AA released by cPLA 2 in response to A␤ oligomers could therefore be involved in synaptic dysfunctions. Moreover, a fraction of cPLA 2 binds to Golgi apparatus in response to calcium and its activity is increased by Ser 505 phosphorylation (Tucker et al, 2009). Previous reports showed that cPLA 2 activity modifies the transport of several proteins between Golgi vesicles and plasma membranes in nonneuronal cell types (Choukroun et al, 2000;Regan-Klapisz et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in free AA released by cPLA 2 in response to A␤ oligomers could therefore be involved in synaptic dysfunctions. Moreover, a fraction of cPLA 2 binds to Golgi apparatus in response to calcium and its activity is increased by Ser 505 phosphorylation (Tucker et al, 2009). Previous reports showed that cPLA 2 activity modifies the transport of several proteins between Golgi vesicles and plasma membranes in nonneuronal cell types (Choukroun et al, 2000;Regan-Klapisz et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…HEPES, pH 7.4, 10 mM, containing 0.16 M KCl and 500 nM Ca 2+ , where and catalytic domain, respectively. Although the cationic site in the catalytic domain is promiscuous in anionic lipid binding ( 21,23,26 ), C1P is the only membrane-embedded anionic lipid that has been shown to increase membrane affi nity of the cPLA 2 ␣ C2 domain ( 19 ). Thus, it is thought that C1P acts as a coincidence detector ( 27 ) to promote the membrane docking of the C2 domain through elongating the membrane residence time ( 19,24,28 ).…”
Section: C1p Stoichiometry Measurementsmentioning
confidence: 99%
“…The role of the phosphorylation of PLA 2 IV␣ in induction of membrane translocation is not fully defined, although a requirement for PLA 2 IV␣ phosphorylation for its full enzymatic activation has been reported by different groups (15,21,22). Serine phosphorylation on PLA 2 IV␣ (Ser-505 or Ser-727) is mediated mainly by the mitogen-activated protein kinases (MAPKs) ERK1/2, and by the stress kinases p38 and JNK, and this has been shown to increase the intrinsic enzymatic activity of PLA 2 IV␣ (23,24).…”
mentioning
confidence: 99%
“…However, this has been revised through more recent studies that have shown that the cationic ␤-groove of the C2 domain can bind to ceramide 1-phosphate on internal membranes (13). Furthermore, the cationic cluster of the PLA 2 IV␣ catalytic domain (Lys-488, Lys-541, Lys-543, and Lys-544) can bind to anionic phospholipids, although the requirement for this interaction for membrane translocation or regulation of enzymatic activity is still under debate (14,15). The majority of these studies have documented translocation of PLA 2 IV␣ to internal cell membranes, such as the nuclear envelope, Golgi complex, and endoplasmic reticulum, whereby PLA 2 IV␣ contributes to the structure and function of these cell compartments (16 -18).…”
mentioning
confidence: 99%